Give Your Life to the Economy: Death Management and Neoliberalism in the Brazil of the Pandemic: espanhol (Palimpsesto, 2022)
This essay is a reflection on the ways in which the Covid-19 pandemic has re-edited and updated the old devices of neoliberalism and the management of death in the Brazilian scene. We start from the discussion on some imperatives and messages repeated since March 2020 in the media that transmit a false idea of freedom of choice in relation to individual protection, while the State, reinforcing the neoliberal ideology and producing feelings of failure, guilt, fear while materially leaving a large part of the population unprotected. Then we articulate notions about neoliberalism and lack of social protection to think about how the management of death has been conducted in the scenario of the pandemic. Finally, we reflect weather insurgency is a possibility or not, promoting the idea that the solidarity networks that have been built are solidarity and class identity based on what resembles us as humans.
Keywords: Pandemic; COVID-19; Death management; Neoliberalism